Comparison of turbulence models for bubble column reactors. (8th June 2017) - Khan, Zoheb; Bhusare, Vishal H.; Joshi, Jyeshtharaj B.
Highlights: CFD simulations of a bubble column are done by using k-ε model, RSM and LES models. Modeling approach is developed for conservation equations of k, ε and RSM. True k-ε model and true RSM are compared against the std. k-ε model and RSM as well as against LES model. The severity of modeling assumptions and their validity for two-phase flow is discussed in great details. Abstract: Though bubble column reactors are widely used in industry, the present design practice is still closer to an art than a desired state of science because of the complexity of its fluid mechanics. The empiricism can be reduced by understanding detailed flow pattern, turbulence characteristics and turbulent structures and their effects on the performance such as mixing and axial mixing in both the phases and rate of heat and mass transfer. For this purpose, in the present work, CFD simulations have been undertaken by using standard k-ε, RSM and LES turbulence models. The cylindrical column having a computational height of HD = 900 mm with inside diameter of D = 150 mm was employed as a bubble column operated at three superficial gas velocities (20, 40 and 100 mm/s). The instantaneous three dimensional velocity field is obtained by means of two phase Eulerian-Eulerian Large Eddy Simulations (LES). The conservation equations for turbulent kinetic energy (k) and the turbulent energy dissipation rate (ε) have been derived from the two fluid governing equations using the Reynolds averaging procedure. This enabled accurate estimation of convective transport, diffusive transport, turbulent transport, production and dissipation of k and ε. These estimations have been compared with the modelled terms of the standard k-ε and Reynolds stress models. The difference in values gives an idea about the severity of assumptions made in these models. An attempt has been made to bring out the implications of simplifying assumptions.